Servicescape And Customers’ Willingness-To-Pay For Vehicle Repairs And Maintenance Services - Kankam-Kwarteng, Collins; Amoateng, Frank (European Scientific Journal, ESJ, 2016)
This research work investigates into the servicescape and customers’ willingness to pay for mechanical services at the Suame Magazine in the Kumasi Metropolis. The study adopted descriptive survey method and the target population was the mechanics and customers of mechanical services in the Suame Magazine in the Kumasi Metropolis. The study conveniently sampled 150 customers who patronize the services of the small scale auto mechanics who repair and maintain vehicles. Questionnaire was used to collect data from the customers. It was realized that signs, symbols and artifacts were not important to customers who go to the Suame Magazine for mechanical services but customers’ perceived ambient conditions and spatial layout as important to them. Customers disagree that Suame Magazine smell badly but they attested that the Suame Magazine is noisy. Suame Magazine has good layout but customers attested that the industrial enclave is always congested. Majority of customers’ relatively perceived charges or price of mechanical services to be relatively as expected and majority (58.0%) of the customers were willing to pay for mechanical services at the Suame Magazine. The customers’ willingness to pay for mechanical services depends on the servicesscape in the Suame Magazine. Mechanical garages with good ambient and spatial layout would have high patronage. The study recommends that mechanics in the Suame Magazine should strategically use servicescape as marketing tool for effective pricing which can influence customer willingness to pay for their services. The mechanical garages should have servicescape policy with specific emphasis on spatial layout and ambient conditions.